ANALISIS RANTAI DISTRIBUSI HASIL PANEN PETANI DI WILAYAH MADURA - Siti Maisaroh Syarif (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
This research aims to provide an in-depth analysis of the distribution patterns of agricultural produce from farmers in the Madura region. Agriculture, a vital sector in Madura, faces distribution challenges concerning infrastructure, the role of intermediaries, and farmers' access to markets. Employing a qualitative descriptive approach with case studies on key commodities such as rice/corn and horticulture/plantation crops, this study gathers primary data through in-depth interviews with farmers, distribution stakeholders, and key informants, alongside field observations. Secondary data are collected from relevant institutions. Qualitative data analysis involves data reduction, presentation, and conclusion drawing, complemented by mapping distribution channels and analyzing the functions of each actor. The findings are expected to identify distribution patterns, the roles of stakeholders, factors influencing distribution efficiency, and the primary challenges encountered in the distribution of agricultural produce, ultimately offering policy recommendations to enhance farmers' welfare and ensure food supply stability in Madura. Penelitian ini bertujuan untuk menganalisis secara mendalam pola pendistribusian hasil panen petani di wilayah Madura. Sektor pertanian yang vital di Madura menghadapi tantangan distribusi terkait infrastruktur, peran perantara, dan akses pasar. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan studi kasus pada komoditas utama seperti padi/jagung dan hortikultura/perkebunan. Data primer dikumpulkan melalui wawancara mendalam dengan petani, pelaku distribusi, dan informan kunci, serta observasi lapangan. Data sekunder diperoleh dari instansi terkait. Analisis data kualitatif meliputi reduksi, penyajian, dan penarikan kesimpulan, dilengkapi dengan pemetaan saluran distribusi dan analisis peran pelaku. Hasil penelitian diharapkan dapat mengidentifikasi pola distribusi, peran pelaku, faktor-faktor yang memengaruhi efisiensi, serta permasalahan utama dalam pendistribusian hasil panen, sehingga memberikan rekomendasi kebijakan bagi peningkatan kesejahteraan petani dan stabilitas pasokan pangan di Madura.